Study Of Compressive And Flexural Strength Of Concrete Using Bima Cement For National Road Reconstruction In Kebumen - Dwiyono Waluyo; Isnaini Lilis Elviyanti; Titi Maemunah; Ahmad Aftah Syukron (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Concrete is an important aspect of building construction, one of which is road construction. Concrete is used for road construction because it has the advantages of high compressive strength, easy maintenance, ease of formation, and easy to obtain components. Road construction using concrete is applied to the reconstruction of the Kebumen South Ring Road, where the Kebumen South Ring Road is a 9.07 km long national road. National roads are arterial and collector roads in the primary road network system that connect provincial capitals, national strategic roads, and toll roads. Therefore, construction on national roads requires strong and good materials on the Kebumen South Ring Road to optimize road use. In this study, the concrete is composed of Bima cement as Portland cement, coarse aggregate from Kebumen, fine aggregate from the Progo River, and water from drilled wells. The admixture was obtained from a Conmix HK 2. Subsequently, all ingredients were mixed using a mixer truck. The concrete mixture was molded into cylinders and blocks. In this study, the average results of the 5-day concrete compressive strength test were obtainedwhich is 373.42 kg/cm2 and 28-day-old concrete is 442.32 kg/cm2. The average result of the 5-day concrete flexural test is50.65 kg/cm2 and that of 28-day-old concrete was 60.73 kg/cm2. The results are in accordance with the general specifications of the Bina Marga, namely, 45 kg.